Forms and Functions of Author Keywords in Theses and Dissertations at the UNESP Institutional Repository (Brazil) - Spotti Lopes Fujita, Mariângela (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie)

(untitled) (Canadian Association for Information Science - Association canadienne des sciences de l'information, 2024)
This research aimed to prepare guidelines for authors by investigating forms and functions of keywords assigned by authors in theses and dissertations defended in 2023 in the Graduate Program in Information Science at Unesp. The exploratory and descriptive study utilized a sample collected in the Unesp Institutional Repository. A corpus of 31 theses and 14 dissertations submitted to the Unesp Institutional Repository comprised a total of 183 keywords in Portuguese without duplicates and an average of 4.7 keywords, considering 213 keywords with duplicates. The analysis results initially identified that the Repository has a tutorial on using the Unesp Thesaurus to control vocabulary and that the authors use natural language to assign keywords. The findings reveal that, out of the 183 keywords, 89 (48%) are exclusive, singular and specific to the area of Information Science, candidates for descriptors in the Unesp Thesaurus. The other 94 keywords (51.3%) have 40 (21.3%) exact descriptors, and the other 54 (29.5%) present forms and functions that serve as examples for inclusion in the tutorial instructions. Based on the results obtained, it is concluded that the percentage of 21% overlap between keywords and descriptors reveals that the Unesp Thesaurus was consulted by the authors when filling out keyword metadata and that the low number of exact descriptors and exclusive keywords indicate that they need to be included as new terms. It is recommended, therefore, to define an Indexing Policy that considers the need for hybrid coexistence between natural language and vocabulary control.